The value of privacy and the choice of limited partners by venture capitalists - Abuzov, Rustam; Gornall, Will; Strebulaev, Ilya A. (Journal of Financial Economics, 2025)
We study how information disclosure concerns shape the choice of limited partners (LPs) by venture capitalists (VCs). Late-2002 court rulings prevented public LPs from providing confidentiality to investment managers. The best-performing VCs, but not other managers, responded by excluding public LPs from their new funds. Lost access reduced public LP returns by 1.6 billion relative to 14 billion of their VC commitments. Legislation reducing disclosure, contracts limiting information access, and added fund-of-funds intermediaries helped restore access. These changes focused on protecting portfolio company information, highlighting the importance of proprietary information for VC investing and the potential costs of transparency.